Infographic Media Increases Learning Interest, Learning Outcomes, and Character of Elementary School Students and Countermeasures Health Problems: Infographic Media Increases Learning Interest, Learning Outcomes, and Character of Elementary School Students and Countermeasures Health Problems - Ketut Ayu Lola Monika; Sariyasa Sariyasa; Nyoman Dantes (JPG: Jurnal Pendidikan Guru, 2023)
The teacher's ability to create learning media is needed to increase interest, learning outcomes, and student character. One of the media that can increase interest, learning outcomes, and student character is infographic media. In addition, infographic media has an effective role in providing education on health problems. Therefore this study examines the role of infographic media in the basic description of schools in increasing student interest, character, and learning outcomes as well as overcoming health problems. This research method is qualitative with the type of literature review research regarding the implementation of infographic media at the basic education level and overcoming health problems. The results obtained from previous research regarding the development of infographic media in increasing interest, learning outcomes, and student character, as well as infographics regarding managing nutritional health problems, organ reproduction, and preventing the Covid-19 Pandemic. The conclusion from this research is that infographics can increase interest in learning, learning outcomes, and the character of students at the basic education level. Infographics can be used as educational media for knowledge of nutrition, adolescent reproductive health, and prevention of pandemic outbreaks. For other research, it is hoped that it can implement infographic media with interesting material and be integrated with local wisdom, learning models, and can be disseminated for educational, economic, and health purposes.